Il buio oltre i partiti? Partecipazione dal basso e partecipazione istituzionale ai tempi della politica reticolare - Raffini, Luca; Viviani, Lorenzo (SocietàMutamentoPolitica, 2011)
Political participation is living a deep process of transformation. Practices, subjects, meanings and goals of participation are changing. In this article, on the basis of a critical assessment of the patterns of change affecting institutional political actors (mainly political parties) and bottom-up forms of participation in the Italian context, we analyze two major instruments implemented to fill the gap between institutional domain and bottom-up participation: primary elections and participative-deliberative processes. Both instruments produce ambiguous and ambivalent effects in terms of empowerment of citizens: they often appear to be more instruments of manipulation and symbolic legitimization than instrument of participation.